The role of mothers in the genealogical lists of Jacob's sons - Smith, D. Charles (Contributions to biblical exegesis and theology, 2018)
Back cover: This work demonstrates that the genealogy of Jacob/Israel was singular and based on the rankings of the four mothers Leah, Rachel, Zilpah and Bilhah. These positions remained in the memory even as the power of various tribes changed over time, guiding the sequenicing of names within the lists. For this reason, the different presentations of the genealogy are not indicative of different Sitz im Leben and do not aid in reconstruction of Israel's early history. A secondary yet equally important discovery is that mothers continue to hold importance beyond the Genesis narrative. This work adds to the growing evidence that mothers in particular, and women in general are vital contributors to their families, to the Promise and to the advancement of the theological message of the Hebrew Bible.